2013
DOI: 10.4028/www.scientific.net/amm.284-287.1473
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Drought Prediction Using Two-Stage SVM

Abstract: The support vector machine (SVM) has been applied to drought prediction and it typically yields good performance on overall accuracy. However, the prediction accuracy of the drought category is much lower than that of the non-drought and severe drought categories. In this study, a two-stage approach was used to improve the SVM to increase the drought prediction accuracy. Four features, (1) reservoir storage, (2) inflows, (3) critical limit of operation rule curves, and (4) the Nth ten-day in a year, were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…With the extracted features for predictors, the GLM and SVM models were applied to forecast the target ASP. The GLM model is a linear model while the SVM model was further tested to check if any performance improvement could be made with more complex models (Chiang and Tsai 2013, Hipni et al 2013, Mokhtarzad et al 2017. For the GLM model, the Gamma distribution was applied, since the employed precipitation data has been known to follow this distribution with a nonnegative domain (Banik et al 2002, Ferraris et al 2003, Hanson and Vogel 2008, Moron et al 2008, Zheng and Katz 2008, Lee 2018.…”
Section: Overall Procedures and Application Methodologymentioning
confidence: 99%
“…With the extracted features for predictors, the GLM and SVM models were applied to forecast the target ASP. The GLM model is a linear model while the SVM model was further tested to check if any performance improvement could be made with more complex models (Chiang and Tsai 2013, Hipni et al 2013, Mokhtarzad et al 2017. For the GLM model, the Gamma distribution was applied, since the employed precipitation data has been known to follow this distribution with a nonnegative domain (Banik et al 2002, Ferraris et al 2003, Hanson and Vogel 2008, Moron et al 2008, Zheng and Katz 2008, Lee 2018.…”
Section: Overall Procedures and Application Methodologymentioning
confidence: 99%
“…Support Vector Regression (SVR) is a popular ML approach in hydrologic forecasting. It has been used in many studies for drought prediction and papers have shown that SVR is a promising tool in drought prediction [19][20][21][22][23][24]. In addition to the use of ML models, researchers also started to produce hybrid models by combining with other techniques, such as ensemble and pre-processing technique.…”
Section: Introductionmentioning
confidence: 99%